N-type doped PEDOT film and preparation method thereof
The preparation of N-type doped PEDOT conductive films by continuous liquid phase polymerization has solved the problem of lack of high-performance N-type PEDOT films in the prior art, achieved the transformation from P-type to N-type and improved conductivity, and has industrial promotion prospects.
Patent Information
- Application Number
- CN202311361625.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-19
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2043-10-19
AI Technical Summary
The existing technology lacks high-performance N-type PEDOT conductive films, and relatively few research on N-type semiconductors, limiting the performance improvement of thermoelectric devices.
The N-type doped PEDOT conductive film is prepared by a continuous liquid phase polymerization method of material. The specific steps include preparing an oxide layer, preparing an EDOT monomer reaction liquid and conducting polymerization reaction, and then performing post-treatment to obtain an N-type doped PEDOT film.
The transformation of PEDOT conductive film from P type to N type is realized, and the conductivity is improved, which proves that the effective preparation of N-type doped PEDOT film is effective and has industrial promotion prospects.
Smart Images

Figure CN119859292A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of thermoelectric materials, and in particular relates to an N-type doped PEDOT conductive film and a preparation method thereof. Background Art
[0002] Thermoelectric materials are new semiconductor materials that use temperature difference to drive the carriers inside the material to move in a directional manner, thereby directly converting thermal energy into electrical energy. They have important application value in the fields of temperature difference power generation and portable refrigeration. Thermoelectric functional materials are green energy materials that can directly convert heat and electricity through the migration of carriers inside solids. Unlike the traditional method of converting chemical energy released by fuel combustion into mechanical energy and then into electrical energy, thermoelectric materials and thermoelectric devices do not require other components to output continuous and stable voltage. The use of traditional energy will lead to environmental pollution, ozone layer depletion and intensification of the greenhouse effect. Thermoelectric materials can directly convert thermal energy into electrical energy, causing almost no pollution or damage to the environment.
[0003] Conductive polymer materials are polymer materials with a conjugated main electron system in the main chain, which can achieve a conductive state through doping (i.e., in order to improve the performance of the material, a small amount of other elements or compounds are added to the material or matrix) and a conductivity of more than 1000S / cm. Their structures have certain commonalities, namely, a conjugated structure with alternating -CC- and -C=C-, which is composed of long-chain carbon molecules connected by sp2 bonds. Due to the characteristics of sp2 bonds, each carbon atom has an unpaired valence electron, and an unpaired bond is formed perpendicular to the sp2 plane. The electron clouds of the unpaired bonds of adjacent atoms are in contact with each other. In this structure, electrons can easily move, so it has a certain conductivity.
[0004] In various thermoelectric devices and electronic components, the pn junction is indispensable. The research and development of high-performance P-type and N-type organic polymer semiconductors has a huge driving force on the entire field of organic electronics. P-type semiconductors are also called hole-type semiconductors. Holes are equivalent to positively charged particles and play a major role in the conduction of this type of semiconductor. In P-type semiconductors, the more impurities are doped, the higher the hole concentration is, and the stronger the conductivity is. N-type semiconductors are also called electronic semiconductors. In N-type semiconductors, the main way to conduct electricity is by free electrons. The more impurities are doped, the higher the free electron concentration is, and the stronger the conductivity is. However, due to the poor environmental stability, steric hindrance effect and limitations of synthesis methods of N-type semiconductors, there are relatively few studies on them.
[0005] Traditional PEDOT films are generally P-type semiconductors, mainly used for transporting holes. For example, the Chinese patent with application number CN202310156271.5 discloses a memristor based on a GaN / PEDOT:PSS planar heterojunction, in which the PEDOT:PSS organic layer is P-type conductive. The Chinese patent with application number CN202110533460.0 discloses an ultra-flexible self-generating yarn and electric fabric, which is a P-type thermoelectric material composed of PEDOT:PSS and ionic liquid. The Chinese patent with application number CN202111210818.2 discloses a PEDOT:PSS / VNO.52O0.26 thermoelectric composite film, which discloses a pn junction barrier that constructs an organic-inorganic composite of P-type PEDOT:PSS and N-type VN0.52O0.26 nanoparticles. In addition, there are currently no reports on pure N-type PEDOT in the literature. Existing literature is all about PEDOT doped with N-type semiconductor materials, such as polyethyleneimine (PEI), such as the document Poly(phthalazinone ether ketone)–Poly(3,4-ethylenedioxythiophene)fiber for thermoelectric and hydroelectricenergy harvesting Chemical Engineering Journal 450(2022)138093.
[0006] In summary, it is necessary to propose a new PEDOT conductive film and a preparation method thereof to prepare a high-performance N-type semiconductor. Summary of the invention
[0007] In view of this, the object of the present invention is to provide an N-type doped PEDOT conductive film and a preparation method and application thereof, and the specific technical scheme is as follows.
[0008] A method for preparing an N-type doped PEDOT conductive film, wherein the N-type doped PEDOT conductive film is obtained by a method of continuous liquid phase polymerization of materials. Specifically, an oxide layer film is first processed, and then the prepared oxide layer film is placed in an EDOT monomer reaction liquid for polymerization reaction. The specific steps are as follows:
[0009] Step 1: preparing a bonding layer on a clean substrate: the materials for preparing the bonding layer include 3-aminopropyltriethoxysilane and polyurethane;
[0010] Step 2: preparing an oxide layer (film): stirring and dissolving an oxidant in deionized water and then preparing the oxidant on the bonding layer obtained in step 1) to obtain an oxide layer, wherein the oxidant is hydrated vanadium pentoxide;
[0011] Step 3: preparing EDOT monomer reaction precursor solution: adding an organic solvent, an acid solution containing hydrogen ions, and EDOT monomer in sequence and mixing them uniformly to prepare an EDOT monomer reaction precursor solution, wherein the volume ratio of each component in the EDOT monomer reaction precursor solution is organic solvent: acid solution: EDOT = 100-900: 1-20: 100-900;
[0012] Step 4: preparing EDOT monomer reaction solution: further adding dimethyl sulfoxide (DMSO) to the EDOT monomer reaction precursor solution prepared in step 3, wherein the volume ratio of the EDOT monomer reaction precursor solution to the dimethyl sulfoxide is 1:0.05-1;
[0013] Step 5: placing the oxide layer prepared in step 2 into the EDOT monomer reaction solution prepared in step 4 to carry out polymerization reaction (EDOT monomer undergoes polymerization reaction in the presence of an oxidant (vanadium pentoxide) and an initiator (acid));
[0014] Step 6: Soak the substrate after the polymerization reaction in step 5 in dilute hydrochloric acid and methanol in turn to remove impurities, thereby obtaining the N-type doped PEDOT conductive film.
[0015] Furthermore, the acid solution containing hydrogen ions includes sulfonic acids, carboxylic acids, hydrochloric acid and the like.
[0016] The above acid solution can provide the hydrogen ions required to promote the polymerization reaction.
[0017] Furthermore, the method for preparing the bonding layer in step 1 includes spin coating, drop coating, blade coating, slit coating or inkjet printing (and any other film forming technology).
[0018] Furthermore, the substrate sheet in step 1 includes a hard substrate and a flexible substrate, including ordinary glass, ITO conductive glass, quartz or PET, etc.
[0019] Furthermore, the molar concentration of the oxidant in step 2 is 0.1-0.5 mol / L.
[0020] Furthermore, the method for preparing the oxidant on the bonding layer in step 2 includes spin coating, drop coating, blade coating, slit coating or inkjet printing (and any other film forming technology).
[0021] Furthermore, the organic solvent in step 3 includes one or more of methanol, ethanol and isopropanol.
[0022] Furthermore, the molar concentration of the EDOT monomer in step 3 is 0.1-6.6 mol / L.
[0023] The N-type doped PEDOT conductive film is prepared by the above preparation method.
[0024] Application of the above N-type doped PEDOT conductive film in the preparation of thermoelectric devices.
[0025] Beneficial technical effects
[0026] The present invention innovatively prepares an N-type doped PEDOT film, realizes the transformation of the PEDOT conductive polymer from a P-type semiconductor (i.e., a hole-type semiconductor) to an N-type semiconductor (electron-type semiconductor), and the Seebeck coefficient of the PEDOT film prepared by the present invention changes from positive to negative, proving that the transformation from P-type to N-type is achieved, and thus electrons can be transmitted. The patent with application number CN202210569859.9 and name "A method for improving the n-type ion thermovoltage performance of PEDOT:PSS film" discloses a method for directly mixing material solutions to prepare a PEDOT:PSS film material with high performance n-type ion thermovoltage. The PEDOT:PSS in the material itself forms a P-type thermovoltage, but PSS will dissociate hydrogen ions. Therefore, after adding a specific material organic guanidine salt, since the organic guanidine salt can provide anions and cations, the concentration of which is much greater than the concentration of hydrogen ions dissociated from PSS, the thermovoltage formed by the migration of hydrogen ions is offset, and the ion thermovoltage is ultimately increased. The present invention directly synthesizes an N-type doped PEDOT film mainly used for transporting electrons by adding DMSO and using a synthesis method of continuous liquid phase polymerization.
[0027] Finally, the method for preparing N-type doped PEDOT film provided by the present invention has simple process, fast preparation speed, low cost, can be realized without special large-scale instruments and equipment, and has good prospects for industrial promotion. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. In all the drawings, similar elements or parts are generally identified by similar reference numerals. In the drawings, each element or part is not necessarily drawn according to the actual scale. Obviously, the drawings described below are some embodiments of the present invention. For those of ordinary skill in the art, other drawings can also be obtained based on these drawings without paying creative labor.
[0029] Figure 1 It is a schematic diagram of the preparation method of the present invention;
[0030] Figure 2 This is a picture of an N-type doped PEDOT film prepared by the method of the present invention;
[0031] Figure 3 The Seebeck coefficient test result of the N-type doped PEDOT film prepared in one embodiment of the present invention;
[0032] Figure 4 The figure shows the test result of the Seebeck coefficient of an N-type doped PEDOT film prepared according to one embodiment of the present invention. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0034] Herein "and / or" includes any and all combinations of one or more of the associated listed items.
[0035] Herein, "plurality" means two or more than two, ie, it includes two, three, four, five, etc.
[0036] It should be noted that, in this article, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, an element defined by the sentence "comprises a ..." does not exclude the existence of other identical elements in the process, method, article or device including the element.
[0037] As used in this specification, the term "about" typically means + / - 5% of the stated value, more typically + / - 4% of the stated value, more typically + / - 3% of the stated value, more typically + / - 2% of the stated value, even more typically + / - 1% of the stated value, and even more typically + / - 0.5% of the stated value.
[0038] In this specification, some embodiments may be disclosed in a format of being within a certain range. It should be understood that such description of "being within a certain range" is only for convenience and brevity, and should not be interpreted as a rigid limitation on the disclosed range. Therefore, the description of the range should be considered to have specifically disclosed all possible sub-ranges and independent numerical values within this range. For example, the range The description of should be considered to have specifically disclosed sub-ranges such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6 etc., as well as individual numbers within this range, for example, 1, 2, 3, 4, 5, and 6. The above rules apply regardless of the breadth of the range.
[0039] The "continuous liquid phase polymerization" described in the present invention is a kind of in-situ polymerization method, which is different from mixed polymerization followed by processing. Specifically, it refers to the sequential processing of the oxide layer and the EDOT monomer, and finally the prepared oxide layer and the EDOT monomer reaction liquid are put together for polymerization; the oxidant and EDOT monomer in the present invention are both processed in the liquid phase.
[0040] Example 1
[0041] The V2O5 in the examples was purchased from West Asia Reagents, and the EDOT monomer was purchased from Adamas Reagents.
[0042] 1) Make the bonding layer
[0043] 3-aminopropyltriethoxysilane (APTES) and polyurethane (WPU) were spin-coated and annealed on the cleaned substrate to obtain a bonding layer;
[0044] During the spin coating process, the spin coating speed is 4000 rpm and the time is 30 s.
[0045] In the annealing process, the annealing temperatures are 120° C. and 80° C., respectively, and the annealing times are 10 min and 30 min, respectively.
[0046] 2) Making the oxide layer
[0047] Dissolving the oxidizing agent hydrated vanadium pentoxide (HVO) in deionized (DI) water by stirring, and then spin coating and annealing on the bonding layer prepared in step 1) to obtain an oxide layer;
[0048] The concentration of the oxidant hydrated V2O5 is 0.1-0.5 mol / L.
[0049] During the dissolving of the oxidant, the stirring rate was 1000 rpm and the dissolving time was 18 h.
[0050] During the spin coating process, the spin coating speed was 1500 rpm and the time was 45 s.
[0051] During the annealing process, the annealing temperature is 80° C. and the annealing time is 10 min.
[0052] 3) Prepare EDOT monomer reaction precursor solution
[0053] 1800 μL methanol (MeOH), 10 μL methanesulfonic acid (MSA), and 200 μL EDOT monomer were added in sequence and mixed evenly to prepare EDOT monomer reaction precursor solution. In this embodiment, the volume ratio of each component is methanol: methanesulfonic acid: EDOT = 900:5:100.
[0054] 4) Prepare EDOT monomer reaction solution
[0055] 200 μL of dimethyl sulfoxide (DMSO) solution was further added to the prepared EDOT monomer reaction precursor solution and mixed evenly to form an EDOT monomer reaction solution; in this embodiment, the volume ratio of the EDOT monomer reaction precursor solution to the dimethyl sulfoxide solution was about 1:0.1.
[0056] 5) PEDOT film formation
[0057] The oxide layer prepared in step 2) is placed in the EDOT monomer solution prepared in step 4) for polymerization reaction for 1 hour.
[0058] 6) Post-treatment of PEDOT film
[0059] The substrate after the reaction was immersed in 0.1% mol / L dilute hydrochloric acid for 10 minutes to remove the residual oxidant and unreacted EDOT, and then immersed in methanol for 10 minutes to obtain an N-type doped PEDOT conductive film.
[0060] Example 2
[0061] 1) Make the bonding layer
[0062] 3-aminopropyltriethoxysilane (APTES) and polyurethane (WPU) were spin-coated and annealed on the cleaned substrate to obtain a bonding layer;
[0063] During the spin coating process, the spin coating speed is 4000 rpm and the time is 30 s.
[0064] During the annealing process, the annealing temperatures are 120° C. and 80° C., and the annealing times are 10 min and 30 min, respectively.
[0065] 2) Making the oxide layer
[0066] Dissolving hydrated V2O5 as an oxidant in deionized (DI) water and then spin coating and annealing on the bonding layer prepared in step 1) to obtain an oxidized precursor;
[0067] The concentration of the oxidant hydrated V2O5 is 0.1-0.5 mol / L.
[0068] During the dissolving of the oxidant, the stirring rate was 1000 rpm and the dissolving time was 9 h.
[0069] During the spin coating process, the spin coating speed was 1500 rpm and the time was 45 s.
[0070] During the annealing process, the annealing temperature is 80° C. and the annealing time is 10 min.
[0071] 3) Prepare EDOT monomer reaction precursor solution
[0072] 1800 μL methanol, 10 μL methanesulfonic acid, and 200 μL EDOT monomer were added in sequence and mixed evenly to prepare an EDOT monomer reaction precursor solution. In this embodiment, the volume ratio of each component was organic solvent: methanesulfonic acid: EDOT = 900:5:100.
[0073] 4) Prepare EDOT monomer reaction solution
[0074] 200 μL of dimethyl sulfoxide (DMSO) solution was further added to the prepared EDOT monomer reaction precursor solution and mixed evenly to form an EDOT monomer reaction solution; in this embodiment, the volume ratio of the EDOT monomer reaction precursor solution to the dimethyl sulfoxide solution was 1:0.1;
[0075] 5) PEDOT film formation
[0076] The oxide layer prepared in step 2) is placed in the EDOT monomer solution prepared in step 4) for polymerization reaction for 1 hour.
[0077] 6) Post-treatment of PEDOT film
[0078] The substrate after the reaction was immersed in 0.1 mol / L dilute hydrochloric acid for 10 minutes to remove the residual oxidant and unreacted EDOT, and then immersed in methanol for 10 minutes to obtain an N-type doped PEDOT conductive film.
[0079] The electrical properties of the N-type doped PEDOT conductive films prepared in Example 1 and Example 2 are shown in the following table:
[0080] Table 1 Conductivity S / cm Seebeck coefficient μV / K Example 1 1.29 -35.31 Example 2 0.67 -20.76
[0081] Both Example 1 and Example 2 successfully prepared N-type doped PEDOT films, whose Seebeck coefficient changed from positive to negative, proving that the transition from P-type to N-type was achieved. The dissolution time of the oxidant in Example 1 and Example 2 was different. From the experiment, the more fully the oxidant was dissolved, the better the conductivity.
[0082] The present invention innovatively adds DMSO during the synthesis of PEDOT, thereby achieving the transformation of the PEDOT film from P-type to N-type. The following table shows the conductivity and Seebeck coefficient results of the PEDOT films prepared with different proportions of DMSO.
[0083] Table 2 Volume ratio of different EDOT monomer reaction precursor solutions to DMSO MeOH:MSA:EDOT:DMSO Conductivity S / cm Seebeck coefficient μV / K 900:5:100:100 0.39 -20.92 900:5:100:300 0.0019 -99.40 900:5:100:500 0.00036 -2.89 500:5:100:500 0.0014 -81.56
[0084] Example 3
[0085] This embodiment provides another example of synthesizing the N-type doped PEDOT film of the present invention.
[0086] Making the bonding layer
[0087] 3-aminopropyltriethoxysilane (APTES) and polyurethane (WPU) were drop-coated on the cleaned substrate to obtain a bonding layer;
[0088] During the drop coating process, the solution is dropped onto the substrate drop by drop and covers the entire substrate, and is then heated at 100° C. on a hot stage until it becomes dry.
[0089] During the annealing process, the annealing temperatures are 120° C. and 80° C., and the annealing times are 10 min and 30 min, respectively.
[0090] 2) Making the oxide layer
[0091] The oxidizing agent hydrated vanadium pentoxide (HVO) is stirred and dissolved in deionized (DI) water and then drop-coated on the bonding layer prepared in step 1) to obtain an oxide layer;
[0092] The concentration of the oxidant hydrated V2O5 is 0.1-0.5 mol / L.
[0093] During the dissolving of the oxidant, the stirring rate is 1000 rpm and the dissolving time is 9-18 hours.
[0094] During the drop coating process, the solution is dripped onto the substrate drop by drop and covers the entire substrate, and is heated to 80°C on a hot stage until it becomes dry.
[0095] During the annealing process, the annealing temperature is 80° C. and the annealing time is 10 min.
[0096] 3) Prepare EDOT monomer reaction precursor solution
[0097] 1800 μL of ethanol, 10 μL of carboxylic acid, and 200 μL of EDOT monomer were added in sequence and mixed evenly to prepare an EDOT monomer reaction precursor solution. In this embodiment, the volume ratio of each component was ethanol: carboxylic acid: EDOT = 900:5:100.
[0098] 4) further adding 200 μL of dimethyl sulfoxide (DMSO) solution to the prepared EDOT monomer reaction precursor solution and mixing evenly to form an EDOT monomer reaction solution; in this embodiment, the volume ratio of the EDOT monomer reaction precursor solution to the dimethyl sulfoxide solution is about 1:0.1;
[0099] 5) PEDOT film formation
[0100] The oxide layer prepared in step 2) is placed in the EDOT monomer solution prepared in step 4) for polymerization reaction for 1 hour.
[0101] 5) Post-treatment of PEDOT film
[0102] The substrate after the reaction was immersed in 0.1% mol / L dilute hydrochloric acid for 10 minutes to remove the residual oxidant and unreacted EDOT, and then immersed in methanol for 10 minutes to obtain an N-type doped PEDOT conductive film.
[0103] Example 4
[0104] This embodiment provides another example of synthesizing the N-type doped PEDOT film of the present invention.
[0105] Making the bonding layer
[0106] 3-aminopropyltriethoxysilane (APTES) and polyurethane (WPU) were coated on the cleaned substrate to obtain a bonding layer;
[0107] During the scraping process, the scraping speed is 5 mm / s.
[0108] During the annealing process, the annealing temperatures are 120° C. and 80° C., and the annealing times are 10 min and 30 min, respectively.
[0109] 2) Making the oxide layer
[0110] Dissolving the oxidizing agent hydrated vanadium pentoxide (HVO) in deionized (DI) water by stirring, and then coating the mixture on the bonding layer obtained in step 1) by knife coating to obtain an oxide layer;
[0111] The concentration of the oxidant hydrated V2O5 is 0.1-0.5 mol / L.
[0112] During the dissolving of the oxidant, the stirring rate is 1000 rpm and the dissolving time is 9-18 hours.
[0113] During the scraping process, the scraping speed is 5 mm / s.
[0114] 3) Prepare EDOT monomer reaction precursor solution
[0115] 1800 μL of isopropanol, 10 μL of carboxylic acid, and 200 μL of EDOT monomer were added in sequence and mixed evenly to prepare an EDOT monomer reaction precursor solution. In this embodiment, the volume ratio of each component was isopropanol: carboxylic acid: EDOT = 900:5:100.
[0116] 4) further adding 200 μL of dimethyl sulfoxide (DMSO) solution to the prepared EDOT monomer reaction precursor solution and mixing evenly to form an EDOT monomer reaction solution; in this embodiment, the volume ratio of the EDOT monomer reaction precursor solution to the dimethyl sulfoxide solution is about 1:0.1;
[0117] 5) PEDOT film formation
[0118] The oxide layer prepared in step 2) is placed in the EDOT monomer solution prepared in step 4) for polymerization reaction for 1 hour.
[0119] 5) Post-treatment of PEDOT film
[0120] The substrate after the reaction was immersed in 0.1% mol / L dilute hydrochloric acid for 10 minutes to remove the residual oxidant and unreacted EDOT, and then immersed in methanol for 10 minutes to obtain an N-type doped PEDOT conductive film.
[0121] The embodiments of the present invention are described above in conjunction with the accompanying drawings, but the present invention is not limited to the above-mentioned specific implementation modes, which are merely illustrative rather than restrictive. Under the guidance of the present invention, ordinary technicians in this field can also make many forms without departing from the scope of protection of the present invention and the claims, all of which are within the protection of the present invention.
Claims
1. A method for preparing an N-type doped PEDOT conductive film, characterized in that: The N-type doped PEDOT conductive film is obtained by a method of continuous liquid phase polymerization of materials, and the specific steps are as follows: Step 1: preparing a bonding layer on a clean substrate: the materials for preparing the bonding layer include 3-aminopropyltriethoxysilane and polyurethane; Step 2: preparing an oxide layer: stirring and dissolving an oxidant in deionized water and then preparing the oxidant on the bonding layer obtained in step 1) to obtain an oxide layer, wherein the oxidant is hydrated vanadium pentoxide; Step 3: preparing EDOT monomer reaction precursor solution: adding an organic solvent, an acid solution containing hydrogen ions, and EDOT monomer in sequence and mixing them uniformly to prepare an EDOT monomer reaction precursor solution, wherein the volume ratio of each component in the EDOT monomer reaction precursor solution is organic solvent: acid solution: EDOT = 100-900: 1-20: 100-900; Step 4: preparing EDOT monomer reaction solution: further adding dimethyl sulfoxide to the EDOT monomer reaction precursor solution prepared in step 3, wherein the volume ratio of the EDOT monomer reaction precursor solution to the dimethyl sulfoxide is 1:0.05-1; Step 5: placing the oxide layer prepared in step 2 into the EDOT monomer reaction solution prepared in step 4 to carry out polymerization reaction; Step 6: Soak the substrate after the polymerization reaction in step 5 in dilute hydrochloric acid and methanol in turn to remove impurities, thereby obtaining the N-type doped PEDOT conductive film.
2. The preparation method according to claim 1, characterized in that The acid solution containing hydrogen ions includes sulfonic acids, carboxylic acids and hydrochloric acid.
3. The preparation method according to claim 1, characterized in that: The method for preparing the bonding layer in step 1 includes spin coating, drop coating, blade coating, slit coating or inkjet printing.
4. The preparation method according to claim 1, characterized in that: The substrate sheet in step 1 includes a hard substrate and a flexible substrate, including ordinary glass, ITO conductive glass, quartz or PET.
5. The preparation method according to claim 1, characterized in that: The molar concentration of the oxidant in step 2 is 0.1-0.5 mol / L.
6. The preparation method according to claim 1, characterized in that: The method of preparing the oxidant on the bonding layer in step 2 includes spin coating, drop coating, blade coating, slit coating or inkjet printing.
7. The preparation method according to claim 1, characterized in that: The organic solvent in step 3 includes one or more of methanol, ethanol and isopropanol.
8. The preparation method according to claim 1, characterized in that: The molar concentration of the EDOT monomer in step 3 is 0.1-6.6 mol / L.
9. The N-type doped PEDOT conductive film prepared by the preparation method according to any one of claims 1 to 8. Claim 10. Use of the N-type doped PEDOT conductive film described in Claim 9 in the preparation of thermoelectric devices.
Citation Information
Patent Citations
Ultra-flexible self-generating yarn, all-fiber-based ultra-flexible thermoelectric self-generating fabric and its preparation method
CN113265880B
A PEDOT:PSS / VN 0.52 O 0.26 Preparation method of thermoelectric composite film
CN113937211B
A method for improving the n-type ionothermal voltage performance of PEDOT:PSS thin films
CN114891321B
A memristor based on a GaN / PEDOT:PSS planar heterojunction and a preparation method thereof
CN116056467B
Method for preparing PEDOT film in large areaw
CN109666265A